Pengaruh Ketepatan Waktu Penyimpanan Berkas Rekam Medis Terhadap Efisiensi Pelayanan Pasien Rawat Jalan Di Puskesmas Tanjung Kabupaten Brebes: Kunnati, Bayu Tri Laksono, Andi Suhenda, Abil Rudi - Kunnati Kunnati; Bayu Tri Laksono; Andi Suhenda; Abil Rudi (Jurnal Persada Husada Indonesia, 2026)
Medical records are crucial documents in healthcare that must be managed appropriately and according to standards. This study aims to determine the effect of the timeliness of storing medical record files on the efficiency of patient services at the Tanjung Community Health Center, Brebes Regency. A quantitative analytical design with a cross-sectional approach was employed. The study population consisted of all outpatient medical records from the internal medicine polyclinic and patients using services at the health center. The sample comprised 66 observed medical records and 30 patient respondents selected through purposive sampling. Data were collected using observation sheets and questionnaires, and analyzed using the Chi-Square test with a significance level of α = 0.05. The results showed a significant effect between the timeliness of medical record storage and patient service efficiency (p = 0.035). In conclusion, timely management of medical records significantly contributes to increased patient care efficiency. This study is expected to provide a basis for health center management to improve their medical record storage system and for medical record staff to be more disciplined in returning files within the required timeframe.